Selected Problems with Diagnostics of Sarcopenia in Long-term-care Facilities for the Elderly - Michal Šteffl; Veronika Houdová; Miroslav Petr; Eva Kohlíková; Iva Holmerová (Karolinum Press, 2014)
Selected Problems with Diagnostics of Sarcopenia in Long-term-care Facilities for the Elderly As the current population gets older, we are learning that some of the diseases and conditions which were formerly perceived as a natural part of the ageing process are actually preventable and curable. Sarcopenia is one of these; it is currently one of the most challenging problems of clinical gerontology. Sarcopenia is a geriatric syndrome that presents as gradual muscle mass loss and decreases in physical performance. It is one of the important factors of frailty. Its treatment is as any other treatment highly dependent on the correct diagnostics. Nevertheless, it seems that latest guidelines for sarcopenia diagnostics considerably neglect real conditions in a number of medical facilities for the elderly, despite the vast increase in the number of studies on its prevalence and the options of sarcopenia treatment carried out in recent years. In this mini review, we shall discuss various diagnostic methods and the possibilities of their real use in clinical practice for the institutionalized elderly. Vybrané problémy s diagnostikou sarcopenia v ústavech dlouhodobé péče pro seniory Protože současná populace stárne, stávají se některé nemocí, které byly dříve vnímány jako přirozená součást procesu stárnutí, významnou výzvou pro vědeckou společnost. Sarcopenia je jednou z těchto nemocí. V současné době je sarkopenie jedním z nejnáročnějších problémů klinické gerontologie. Sarcopenia je geriatrický syndrom, který se projevuje postupnou ztrátou svalové hmoty, silové schopnosti a snížením fyzické výkonnosti. Je to jeden z důležitých faktorů stařecké křehkosti. Její léčba je tak jako jakákoliv jiná léčba vysoce závislá na správné diagnostice. Přesto se zdá, že poslední pokyny pro diagnostiku sarkopenie výrazně zanedbávají skutečné podmínky v řadě zdravotnických zařízení pro seniory a to navzdory obrovskému zvýšení počtu studií zabývajících se prevalencí a možnostmi léčby sarcopenie, které byly provedené v posledních letech. V této mini recenzi budeme diskutovat o různých diagnostických metodách a možnostech jejich skutečného použití v klinické praxi při léčbě sarkopeníí ohrožených institucionalizovaných seniorů.